Evaluation of phosphine gas as a quarantine treatment for obscure mealybug for export markets - Cichon, Liliana; Garrido, Silvina Alejandra; Gomez, Roberto Carlos; Fernandez, Dario Eduardo; Argañaraz, Luis Manuel; Gastaminza, Gerardo (ISHS, 2025)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010